Emicizumab Improves Ex Vivo Clotting Function in Patients with Mild/Moderate Hemophilia A - Nakajima, Yuto; Nogami, Keiji; Yada, Koji; Furukawa, Shoko; Noguchi-Sasaki, Mariko; Hirata, Michinori; Shima, Midori (Thrombosis and Haemostasis, 2020)
Background Emicizumab prophylaxis is a promising treatment that reduces bleeding events in severely affected patients with hemophilia A (PwHA). It is anticipated that emicizumab could be similarly effective in mild/moderate PwHA (PwMHA) although this effect has not been investigated.Aim We evaluated ex vivo coagulant effects of emicizumabin PwMHA.Methods Clot waveform analysis (CWA) triggered by prothrombin time/activated partial prothrombin time-mixed reagents was utilized to examine coagulant effects of emicizumabin factor (F)VIII-deficient plasma mixed with recombinant (r)FVIIIand in native plasmas from 16 PwMHA. The CWA parameter, adjusted-|min1| (Ad|min1|), was used. Increases in Ad|min1| (ΔAd|min1|) mediated by emicizumab were calculated from the slopes of regression lines in the presence of rFVIII.Results Ad|min1| in FVIII-deficient plasma with various concentrations of rFVIII negatively correlated with ΔAd|min1|by adding emicizumab, and these data were defined as standard reference values. Ad|min1| (4.57 ± 0.50) in 16 PwMHA increased to 5.05 ± 0.54 and 5.37 ± 0.60 by adding emicizumab at 50 and 100 μg/mL, respectively, but remained lower than the normal range (7.22 ± 0.21). ΔAd|min1| levels were 1.5 to 2-fold higher in five cases and 0.4 to 0.6-fold lower in four cases, compared with reference values determined by rFVIII. In some cases, genetic analyses suggested that specific point mutations could have contributed to these findings. Further studies using rFVIII mutants indicated, however, that the differences in ΔAd|min1| were not related to individual FVIII gene defects.Conclusion Emicizumab enhances coagulation potential in PwMHA. Assessment of ex vivo coagulant activity of emicizumab could be helpful for predicting coagulant potentials prior to treatment in these patients.
Keywords: hemophilia A; mild/moderate type; clot waveform analysis; emicizumab; factor VIII